Effect of urea and molasses fermented cassava pulp on rumen fermentation, microbial population and microbial protein synthesis in beef cattle - Thitima Norrapoke; Tanitpan Pongjongmit; Suban Foiklang (Journal of Applied Animal Research, 2022)
This study aimed to investigate the effects of fermented cassava pulp with urea and molasses on feed intake, nutrient digestibility, rumen fermentation and microbial protein synthesis. All brahman crossbred beef cattle were randomly assigned according to a 4 × 4 Latin Square Design to receive four dietary treatments; cassava pulp (control), cassava pulp fermented with urea 4%, cassava pulp fermented with molasses 4%, and cassava pulp fermented with urea 4% and molasses 4%. All animals were fed concentrate pellet at 1.5% BW and supplemented 0.5% BW of cassava pulp. The results showed that rumen NH3-N concentration was increased in cattle fed with both cassava pulp fermented with urea and/or molasses (P < 0.05). The total VFA was not affected by dietary treatments while there was an increase in propionic acid when cattle were supplemented with fermented cassava pulp. However, methane production and protozoal population were lower in treatments with fermented cassava pulp (P < 0.05). Feeding of fermented cassava pulp resulted in an increase in microbial protein synthesis (P < 0.05). Based on the present findings, it could be concluded that fermented cassava pulp with urea and molasses can increase propionic acid, microbial protein synthesis while reducing protozoal population and CH4 production.